An aircraft design for maintainability methodology integrated with computer aided design - Lockett, Helen L.; Estefani, J.; Reytérou, E. (Cranfield University, 2012)
Maintenance typically represents 10 – 25% of the direct operating cost of an aircraft and minimizing maintenance cost is therefore an important driver for aircraft design. This paper presents a methodology for Design for Maintainability that uses an accessibility checklist for maintainability assessment at the preliminary design stage, and a maintenance task time prediction method that can be used at the detailed design stage. Both elements of the methodology use Computer Aided Design to assess virtual maintenance operations for accessibility and human performance. The methodology provides a basis for the comparison of design alternatives with respect to maintainability.
Keywords: aircraft design; maintainability; computer aided design; Maynard Operation Sequence Technique (MOST); task time